SIMULATION AND MANUFACTURE OF CLOSURE COMPONENTS FOR AN AUTOMOTIVE INDUSTRY - MURUGAN N; NAGA DHATSHANA R (International Journal of Innovations in Engineering Research and Technology, 2021)
Manual welding and hemming processes don’t deliver higher speeds and efficiency resulting in reduced production rate. Hence, robotic hemming and welding processes are to be implemented to overcome the risk involved in manual welding and achieving greater efficiency. Based on the present system layout in a local automotive industry, a virtual work cell was created with various robot models, fixtures and work tools like clamps, welding guns, rollers, etc. The robot operations were simulated and checked for collision, zoning and the cycle time which was estimated for both the virtual and real work environment. The simulated work cell was replicated in the real environment and checked for any discrepancies with the virtual work cell. The estimated total process time of various processes carried out in the closure panel assembly line by both the automated method and conventional method was compared and the percentage reduction in the total process time was determined.